Technologie informacyjne w nauczaniu geometrii w szkole podstawowej - Maj, Monika; Falkiewicz, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Celem pracy jest odpowiedź na pytanie, czy nowoczesne technologie służą lepszemu przyswajaniu wiedzy z zakresu geometrii przez dzieci. Przedstawione wyniki badań podają odpowiedź z punktu widzenia nauczyciela matematyki w szkole podstawowej.

The aim of the work is to answer the question whether modern technologies serve to better acquire knowledge in the field of geometry by children. The presented research results give the answer from the point of view of the math teacher in primary school.
Information technologies in learning geometry in primary school
Keywords: informatyka; matematyka; szkoła podstawowa; edukacja; wiedza; computer science; maths; prymaty school; education; knowledge